Economic Valuation of Mangrove Ecosystem for Sustainable Management in South Lembar District, West Lombok Regency - Muhammad Dzakir Maulana; Immy Suci Rohyani; Isrowati (Journal of Biology, Environment, and Edu-Tourism, 2025)
The mangrove ecosystem of Lembar Selatan Village, Lembar District, West Lombok Regency, has an important role in maintaining ecological balance and is a source of direct and indirect income for the people of Lembar Selatan Village. This study aims to calculate and analyze the use value (utility value) and non-use value (non-utility value) of the mangrove ecosystem of Lembar Selatan Village. The method used is based on market prices for direct benefits, replacement costs for indirect benefits, TCM (travel cost method) for optional benefits, WTP (willingness to pay) for legacy benefits, and benefit transfer for existence benefits. The results of the study showed that the mangrove ecosystem of Lembar Selatan Village has a total economic value of Rp. 149,146,103,968.44/72ha/year. The use value of Rp. 148,276,491,851.44/72ha/year was obtained from the total direct benefit value of Rp. 18,748,080,000/72ha/year, indirect benefits of Rp. 127,739,091,851.44/72ha/year, optional benefits of Rp. 118,560,000/72ha/year. Non-use value is obtained from the value of inheritance benefits of Rp. 792,450,000/72 ha/year, and existence benefits of Rp. 77,162,117/72 ha/year. The total use value obtained in the mangrove ecosystem of Lembar Selatan Village is Rp. 148,276,491,851.44/72 ha/year and the total non-use value is Rp. 869,612,117/72 ha/year. The use value obtained is greater than the non-use value caused by the use of use value can be felt by the community directly or indirectly, but if the non-use value cannot be felt now because it is for the future, such as inheritance value and existence value.